Microcredit and the household food security of the fish farmers: evidence from rural Bangladesh. Issue 8 (17th November 2022) - Mahmud, Kazi Tanvir; Parvez, Asif; Ahmed, Shadman Sahir; Rafiq, Farhana
ABSTRACT: The credit-constrained poor fish farmers in Bangladesh usually have limited access to formal credit institutions. As a result, NGOs took the effort to provide collateral-free microcredit support for the fish farmers to tide over their credit-related problems. This study empirically assesses the impact of microcredit on the household food expenditure of fish farmers. The empirical results challenge the existing literature that access to credit increases the food expenditure of poor fish farmers. However, household assets played a pivotal role in increasing the food expenditure capacity of the fish farmers.